Types of housing in the area of the General Urban Plan of Niš - Maksić Mulalić, Milica; Manić, Božidar; Njegić, Tanja (Arhitektura i urbanizam, 2023)
The paper analyzes the types of housing in the area of the General Urban Plan of Niš. There are 5 types of housing singled out: city-type family housing, suburban-type family housing, mixed housing zones, multi-family housing from the pre-war and post-war period, and newly built multi-family housing. These types of housing were analyzed in the paper based on 18 previously defined criteria. The criteria took into account the characteristics of the macro-location (location, formed traffic matrix, availability of contents, quality of the environment, etc.), as well as urban parameters at the block level (size and geometry of the plot, number of floors, parking, architecture, construction quality, etc.). Mutual similarities and differences of the analyzed housing types are determined, as well as essential changes that occurred in the post-socialist transition period, in order to define possible directions for the improvement of planning regulations and housing construction.